Editorial (American Journal of Islam and Society, 1996)
In this issue of AJISS we present a diverse number of articles that dealwith a wide range of issues. The thorny and continuously debated relationbetween Islam and the West is the subject of four contributions: RalphCoury’s “A Neoimperial Discourse on the Middle East,” Charles Butterworth’s“On Others as Evil: Toward a Truly Comparative Politics,” Ali A.Mazrui’s “Islam in a More Conservative Western World,” and M. HazimShah ibn Abdul Murad’s review essay on “Islam and ContemporaryWestern Thought.”Commonly, it is the reports of missionaries, travel literature, colonialistmemoirs, or orientalist texts that have been the main field of research forstudying western attitudes toward Islam. In contrast, Ralph Coury’s contributiontakes an uncommon approach to exploring these attitudes by usingthe works of Paul Bowles, the American expatriate novelist, as a principleresearch tool. Bowles has spent most of his productive life in Morocco,where the Arab and Islamic constitutional elements of the people and theirlife make up the fabric and background of his novels and his other writings.In this penetrating analysis of Bowles’s views of Islam and of Arabs, Courylinks the inner psychodramatic self of the novelist to his political and culturalunconscious in order to provide an alternative insight to his works.Looking at the issue from a different perspective, Charles E. Butterworthbrings to the fore a variant reading of the western cultural heritage.Butterworth begins his study by emphasizing that, as far as the relationbetween Islam and the West is concerned, “for exchange to be fruitful, eachparty needs to look at the best in his or her own tradition, rather than at theworst, or even the ordinary, and ask that the interlocutor do the same for hisor her tradition.” By this, Butterworth endeavors to recover the other, thelost and forgotten dimension of the westem mind: the mind of Homer, ofSocrates, and of Albert Camus. It is the tentative mind that is seen as relevantto Islamic-western dialogue, the self-doubtful mind, where the humantraits of wisdom, courage, moderation, and justice lend themselves veryprominently to a particular part of the western discursive tradition.Instilled with the wisdom and insight of a keen observer of the humancondition, Ali A. Mazrui treats the subtle ideo-political transformation ofthe West as well as that of the Muslims living in the West, not as studentsor travelers, but as members of this society. His findings rest on three main ...